An analysis of the use of gerunds in academic essays of university students - Md. Idrus, Norazah; Abdul Malik, Faridah (Kulliyyah of Languages and Management, International Islamic University Malaysia, Pagoh, 2019)
At higher educational institution, students are expected to have acquired a certain level of English language mastery to fulfill the demands of academic writing. One of the grammatical items that is crucial in expressing the students’ ideas and opinions is gerund. The use of gerunds in academic essay helps students to be more precise and concise. However, this poses a problem as students do not use gerunds as frequently and as correctly as expected. Thus, this study intended to investigate the use of gerunds and to determine the functions of gerunds used in students’ academic essays. In order to explore the uses and functions of gerunds, data were collected from students’ academic essays. These data were analysed using textual analysis based on the framework of Seiss (2008). The findings show that on average, only a minimal of two gerunds were used in an essay and in total, there were 260 gerunds used in 100 essays. Another finding revealed that students used all functions of gerunds except It-Replacement function. This study implicates a better understanding on the use of gerunds (or lack of it) in academic essays and on the teaching of academic writing at tertiary level.